A Methodological Framework for Evaluating Smart Transport Applicability in Algiers - Labri, Naima; Baziz, Amal (Communications - Scientific Letters of the University of Zilina, 2022)
Intelligent transport systems (ITS), deriving from smart mobility concept, are emerging as a solution to transportation problems using information and communication technologies (ICT) to improve the transport performance and quality. The authors of this work aimed to propose a framework that evaluates applicability of ITS in the public transport sector, using Algiers as a case study and to discover eventual barriers to their implementation. The proposed framework is supported by literature contributing to the question of what barriers are encountered in developing versus developed countries when implementing ITS, this type of ignorance of contextual difficulties leads to calls for conceptual research in this regard. The methodology was illustrated using a matrix of indicators and measuring the applicability index. The result highlighted several barriers to technology adoption in Algiers public transport system and requires acting as a priority on governance and performance indicators according to Algiers context as a North African city.
Keywords: ITS (Intelligent transport systems) Algiers; public transport (PT); smart mobility; framework